Electret effect in intercalated crystals of the A³B⁶ group - Grygorchak, I.; Voitovych, S.; Stasyuk, I; Velychko, O.; Menchyshyn, O. (Condensed Matter Physics, 2007)
Measurements of dielectric properties of Ni-intercalated GaSe and InSe have been performed. The present study is aimed at the investigation of the low-admixture region where the intercalation induced electret effect occurs. The effect exhibits pronounced peak-like concentration dependences and a non-monotonous temperature behaviour with maximum magnitudes at low temperatures. Intercalation leads to over tenfold increase of dielectric permittivity over the whole measured frequency range with up to several orders at low frequencies for GaSe. Temperature dependences of the permittivity demonstrate well-defined peaks with localizations and heights strongly depending on the concentration. A microscopic model of order-disorder type has been proposed that considers redistribution of intercalant atoms between non-polar octahedral and polar tetrahedral positions in the crystal van der Waals gaps. Such a redistribution can occur in the form of phase transition to the polar phase (corresponding to the electret effect) which is stabilized by the internal field. For the case of octahedral positions being more preferable, the model predicts a peak-like dependence of the crystal
polarization on chemical potential due to passing through the interjacent polar phase in accordance with the measured behaviour of the electret effect. The calculated temperature dependences of dielectric susceptibility qualitatively reproduce experimental results for permittivity as well. Проведено вимiрювання дiелектричних властивостей GaSe та InSe, iнтеркальованих Ni. Дана робота спрямована на дослiдження в областi низьких концентрацiй домiшки, де iснує породжений iнтеркаляцiєю електретний ефект. Для нього характернi вираженi пiкоподiбнi залежностi вiд концентрацiї та немонотонна поведiнка при змiнi температури, де максимальнi амплiтуди досягаються для її низьких значень. Iнтеркаляцiя приводить до понад десятикратного зростання дiелектричної проникливостi у всьому вимiряному частотному дiапазонi, а при низьких частотах для GaSe – збільшення на кiлька порядкiв. Температурнi залежностi проникливостi демонструють виразнi пiки, розташування та висота яких сильно залежать вiд концентрацiї. Запропоновано мiкроскопiчну модель типу лад-безлад, що враховує перерозподiл атомiв iнтеркалянта мiж неполярними октаедричними та полярними тетраедричними позицiями у ван-дер-ваальсових щiлинах кристалiв. Такий перерозподiл може вiдбутися у формi фазового переходу до полярної фази (що вiдповiдає електретному ефекту), яка стабiлiзується внутрiшнiм полем. Для випадку, коли октаедричнi позицiї бiльш вигiднi, модель передбачає пiкоподiбну залежнiсть поляризацiї кристалiв вiд хiмiчного потенцiалу, спричинену проходженням через промiжну полярну фазу, що узгоджується з вимiряною поведiнкою електретного ефекту. Розрахованi температурнi залежностi дiелектричної сприйнятливостi теж якiсно вiдтворюють експериментальнi результати для проникливостi.